Sustainable Chicken Eggs from Cage-Free and Free-Range Production Systems (Consumer Satisfaction in Yogyakarta - Dinda Dewi Aisyah; Dhika Cahyasita; Mochamad Mussodaq (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2026)
The distribution of food ingredients with sustainable claims from cage-free and free-range production systems is currently increasing. Eggs, as one of the affordable and easily accessible food ingredients for the community, have been developed into products with sustainable value. The study aims to identify the socio-demographic characteristics of sustainable egg consumers, investigate consumer satisfaction levels, and map the attributes that reflect the urgency and performance inherent in egg products with sustainable claims. Data were collected in July 2024 through structured interviews with up to 100 consumers in the Special Region of Yogyakarta. Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) were applied in this study. The results show that respondents were mostly of productive age, had small households, and belonged to low- to middle-income groups, with generally moderate egg consumption levels. At the same time, the analysis shows that consumer satisfaction with eggs bearing sustainable claims is relatively high. The attributes of freshness, variety of egg types, and the added value of Omega-3 are considered the most important and satisfying attributes. In developing their products, marketers need to improve the performance of egg size, packaging, and the number of eggs per package.